Produtividade de madeira do eucalipto correlacionada com atributos do solo visando ao mapeamento de zonas específicas de manejo - Passos e Carvalho, Morel de [UNESP]; Mendonca, Veridiana Zocoler de [UNESP]; Belchor Lages Pereira, Francisco Cezar [UNESP]; Arf, Marcelo Valentini [UNESP]; Kappes, Claudinei [UNESP]; Dalchiavon, Flávio Carlos (Universidade Federal de Santa Maria (UFSM), 2012)
The perfect spatial intervention to manage the cultivation of the land, deriving from specific regions of the soil mapping, increases the agricultural productivity, as well as its clear gain. The relationships, spatial and Pearson, between eucalyptus data plant with some physical and chemical attributes of soil, in the growing season of 2011, in Selviria County, Mato Grosso do Sul State, Brazil (20 degrees 20' S lat.; 51 degrees 24' W long.), were studied in order to obtain the one that could have the best relationship in order to improve the wood productivity. Thus, a geostatistical grid was installed for the soil and plant data collection, it contained 120 sample points, in plantation of Eucalyptus camaldulensis of 2 years old. The soil was a Dystrophic Red Latosol (Haplic Acrustox) whit slope of 0.025m m(-1). Due to their excellent relationship with wood productivity, the basis diameter of the crown and the bulk density showed management specific regions of soil whit high relation to eucalyptus wood productivity.
Eucalyptus wood productivity correlated with soil attributes aiming the mapping of management specifics regions
Keywords: soil management; precision agriculture; Eucalyptus camaldulensis